Genome sequence and analysis of a broad-host range lytic bacteriophage that infects the Bacillus cereus group - El-Arabi, Tarek F (BioMed Central, 2013)
BACKGROUND: Comparatively little information is available on members of the Myoviridae infecting low G+C content, Gram-positive host bacteria of the family Firmicutes. While numerous Bacillus phages have been isolated up till now only very few Bacillus cereus phages have been characterized in detail. RESULTS: Here we present data on the large, virulent, broad-host-range B. cereus phage vB_BceM_Bc431v3 (Bc431v3). Bc431v3 features a 158,618 bp dsDNA genome, encompassing 239 putative open reading frames (ORFs) and, 20 tRNA genes encoding 17 different amino acids. Since pulsed-field gel electrophoresis indicated that the genome of this phage has a mass of 155-158 kb Bc431v3 DNA appears not to contain long terminal repeats that are found in the genome of Bacillus phage SPO1. CONCLUSIONS: Bc431v3 displays significant sequence similarity, at the protein level, to B. cereus phage BCP78, Listeria phage A511 and Enterococcus phage ØEF24C and other morphologically related phages infecting Firmicutes such as Staphylococcus phage K and Lactobacillus phage LP65. Based on these data we suggest that Bc431v3 should be included as a member of the Spounavirinae; however, because of all the diverse taxonomical information has been addressed recently, it is difficult to determine the genus. The Bc431v3 phage contains some highly unusual genes such as gp143 encoding putative tRNA(His) guanylyltransferase. In addition, it carries some genes that appear to be related to the host sporulation regulators. These are: gp098, which encodes a putative segregation protein related to FstK/SpoIIIE DNA transporters; gp105, a putative segregation protein; gp108, RNA polymerase sigma factor F/B; and, gp109 encoding RNA polymerase sigma factor G.